PROFIL BERPIKIR KREATIF DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Susanti, Dian (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2016)
This research will be based in the background by the problems often encountered by students that is completing a math problem, in particular the question of the story. Most students consider the intricate story is primarily a matter which could not be resolved in a practical way. Formulation of the problem in this research is "how the profile of the creative thinking of students of class VIII C 1 PGRI Surabaya in JUNIOR HIGH solve math story?”.The purpose of this research is to know the profile of the creative thinking of students of class VIII C 1 PGRI Surabaya SMP in solving math story problem, especially in terms of his thinking ability. the thought process is a process that consists of the reception of information (from outside or in the students), management, storage, and callbacks that information from the student's memory. This means that in thinking someone is sure doing a process to find a conclusion or completion of something that thought. Thought process in this study are grouped into three conceptual thought process, that is the way of thinking of students in solving a problem using concepts that have been learned. Semikonseptual, that is the way of thinking of students in solving a problem using concepts that have been learned, but not complete. Computational, i.e. a way of thinking of students in solving a problem without using concepts that have been learned. In research done by using written tests, documentation, and interviews.The subject in this study consisted of 6 students consisting of two people of high ability students, two students are capable of being, and two low-capable students. The data obtained by means of the previous semester raport values obtained, test essay be reserved story sdah validated by two validator, and then in kroschek with the interview. The results showed that the thought process of a group of high-ability students tend to think conceptually, capabilities are likely to be in the process of thinking is semikonseptual, whereas the thought processes of a group of low ability students tend to be on Computational thinking processes. Keywords: process of thinking, conceptual, computational, semikonseptual.